PEMANFAATAN ARANG DARI BATANG POHON DENGAN PEREKAT PVAC UNTUK DEGRADASI LIMBAH METHYLENE BLUE - Adelina Ryan Candra Dewi; Masturi Masturi; Ian Yulianti; Agus Ulin Nuha (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The dye is widely used in the industry which came dye textiles, plastics, and batik. Results of waste as a result of the dye can cause poisoning which is very dangerous. Waste methylene blue into one of the results of waste textile color. Charcoal from waste tree trunks using adhesives PVAC successfully made into a carbon that is able to absorb the waste dye methylene blue. Making carbon with PVAC adhesive into new things that are simple to absorb waste dye and easy to do by the general public without the use of laboratory equipment. The purpose of this study was to determine the effect of variation of immersion time and the mass of charcoal to the transmittance and absorption of waste degradation methylene blue 67 ppm. Degradation of methylene blue waste generated by providing independent variable mass quantities of charcoal trunk as much as 3g, 6g, 9g, 12g, 15g and 18g and variable time soaking for 12 hours and 36 hours. The concentration of methylene blue before and after irradiation was measured using a UV-Vis spectrometer. The results showed that the soaking time and the amount of carbon affect the absorbance and transmittance of methylene blue waste. The more the sheer number of masses of charcoal and charcoal long soaking time, giving the plot a graph of absorbance down and plot a graph of transmittance rose nearly perfect degradation.Keywords: Carbon, PVAC, Waste methylene blue, absorbance, transmittansion.